Atlas of the Mammalian Ovary Morphological Dynamics and Potential Role of Innate Immunity - Spanel-Borowski, Katharina; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
In the era of molecular biology, an atlas that allows a rapid understanding of the complexity of ovarian processes is urgently needed. In this book, the author draws upon her own research, conducted over the past three decades, to provide a unique compilation of high-quality illustrations that offer illuminating insights in a readily accessible form. The ovarian follicles, the corpus luteum, and the interstitial cortex are presented as precisely controlled homeostatic compartments. Physiologic cell death forms and leukocyte subtypes are clearly depicted, and the various steps in the ovulatory process are demonstrated in detail. Further topics addressed include the microvascular bed, the plasticity of intraovarian nerves as part of the remodelling processes in the polycystic and the menopausal ovary, and the role of cytokeratin-positive cells (of steroidogenic or microvascular origin) as messengers of innate immunity. This atlas will be a fascinating and informative resource for both trainees and more experienced professionals.
Introduction -- Follicle stages and follicular atresia without and with irradiation -- Follicular atresia as proliferative and inflammatory event -- Cortex and cellular stromolysis -- The ovulatory period as acute inflammatory response to oxidative stress and follicle cell harvest -- Corpus luteum cycle with focus on capillary sprouting and regression, eosinophils and KIT-positive cells -- Intraovarian oocyte release (IOR) with severe tissue damage -- Vascular stromolysis and vascular luteolysis for bulk tissue removal -- Polycystic and postmenopausal ovaries and negligible mast cells -- Cytokeratin-positive cells as dendritic-like cells and potential albumin-coexpression in follicles and corpus luteum -- Aspects of immunological control, novel concepts, challenges and clinical perspectives.
Keywords: Medicine; Immunology; Human anatomy; Gynecology; Endocrinology; Pathology; Reproductive Medicine; Medicine & Public Health; Gynecology; Reproductive Medicine; Endocrinology; Immunology; Pathology; Anatomy